PENGARUH MEDIA VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR IPA DITINJAU DARI KEAKTIFAN SISWA - Dwi Yunita; Astuti Wijayanti (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2017)
This research is aimed to know the impact of using video as a media toward the learning result of sciences for students in class VII in SMPN 1 Turi on 2016/2017 which is looked by the student’s creativity. This research is quasi experiment. The object of this research is the student’s result. The technique of data collection is using test, questioner and documentation techniques. Instrument test is containing with 30 multiple-choice questions, and questioner instrument is containing with 20 statements. As the result, the researcher obtained Fcalculate = 19,747 and p = 0,000, the average of learning result is 20,78, the average of questioner is 60,09. Based on the average of learning result and questioner, then there is an impact by video as a media toward the learning result of sciences for students in class VII which is looked by the student’s creativity.